Nutritional and Nutraceutical Properties of Mexican Traditional Mole Sauce - Rafael Campos-Montiel; Gabriela Medina-Pérez; Edgar Vázquez-Nuñez; Laura Afanador-Barajas; Iridiam Hernández-Soto; Gulzar Ahmad Nayik; Lucio González-Montiel; Mohamed Alkafafy (Molecules, 2022)
Mole sauce is one of the traditional Mexican foods; it is a complex mixture of ingredients of diverse origins that directly influence its nutritional value. The objective of this study was to investigate the antioxidant properties and nutritional components in five varieties of mole from Hidalgo in Mexico namely verde (V), ranchero (R), almendrado (A), casero (C), and pipian (P). Proximal chemical analysis and determination of the color index and the content of total starch, dietary fiber, mineral content (Ca, Na, K, and Mg), total phenolic content, and antioxidant activity by ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) and DPPH (2,2-diphenylpicrylhydrazyl) were carried out. All the five varieties of mole reported less than 25% moisture content while fat content varied from 42.9% to 58.25%. The color index ranged from a deep orange to a deep red color. A fair percentage of dietary fiber was found in all mole varieties with a low amount of starch as well. The presence of mostly insoluble dietary fiber, high phenolic content (36.13–79.49 mg GAE/100 g), and high antioxidant activity could be considered important strengths to boost the consumption of these traditional preparations. This research will contribute to a better scientific knowledge of traditional Mexican sauces as functional foods or nutraceuticals that could be used to avoid health disorders.